Correspondence of nurses' and physiotherapists' records for orthopedic patients with the Nursing Outcomes Classification - Bruna Engelman; Marcos Barragan da Silva; Miriam de Abreu Almeida
ABSTRACT Objective: To evaluate the correspondence of the terms found in nurses' and physiotherapists' records for orthopedic patients with the Nursing Outcomes Classification (NOC). Method: A descriptive study carried out in a university hospital in southern Brazil. The sample consisted of 392 records of 49 patients submitted to Total Hip Arthroplasty (THA). Data collection was retrospective in the electronic health record. Data was analyzed and compared with the NOC outcomes using the cross-mapping method. Result: The most prevalent outcomes were the following: Pain Level, Falls Occurrence and Mobility. There was sharing of outcomes between the two categories, except for Falls Occurrence and Respiratory Status. Conclusion: Standardizing nurses' and Physiotherapists' records according to the NOC can improve the quality of the clinical documentation of the outcomes of patients undergoing THA.